ASSESSMENT OF RADON CONCENTRATIONS IN WATER SOURCES FROM SABON GARI LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA - Jibril, M. K.; Garba, N. N.; Nasiru, R.; Ibrahim, N. (FUDMA JOURNAL OF SCIENCES, 2021)
Radon concentration in water is one of the major problems of radiation protection in recent years. This work assessed the radon concentration in water sources from Sabon Gari, local government area, Kaduna State. The water samples were collected and analyzed using Liquid scintillation counter (Tri-Carb-LSA1000). The overall mean radon concentration of the waters samples was found to be 14.9 BqL-1, which is higher than the maximum permissible limit of 11.1 BqL-1 by USEPA and the world average value of 10 BqL-1 by UNSCEAR and WHO. The overall Annual effective dose (AED) due to inhalation of radon is calculated to be 37.6 Î¼Svy-1. This value is less than the permissible limit of 100 Î¼Svy-1 set by WHO. Also, the overall AED due to ingestion is estimated as 109.0, 154.2, and 180.4 Î¼Svy-1 respectively for both Adult, children and Infant, which is slightly higher than the WHO permissible limit of 100 Î¼Svy-1 for adults and less than the permissible limit of 200 Î¼Svy-1 for children. This result shows that the inhabitants of Sabon Gari local government are safe from any radiological health related effects that may result from the inhalation of radon gas. Also, both Children and Infant are safe from any immediate radiological health risk, but for Adults, consuming any of the water sources (Well, Borehole and Surface) over a prolong period of time is not completely safe and may result in radiological health hazard